Transforming Malaysia dominant and competing paradigms - Milner, A.C. (Anthony Crothers) 1945-; Abdul Rahman Embong; Tham, Siew Yean (UPCC book collections on Project MUSE, 2014)
This book, which engages with both the race paradigm and its opponents, warns that change is likely to come slowly - but is not impossible. Malaysia's race paradigm is a man-made ideological construct - one that has been contested in the past, and could realistically be contested in the future